Cell-type-specific mechanisms of transcriptional repression by the homeotic gene products UBX and ABD-A in Drosophila embryos. - Appel, B (1993)
The homeotic genes of Drosophila melanogaster, which are required for specification of segmental identities, encode proteins capable of regulating gene expression. We have chosen to study the organization and function of a regulatory target in an attempt to learn how homeotic gene products provide appropriate transcriptional controls. We identified 30 common binding sites for the proteins encoded by the Ultrabithorax (Ubx) and abdominal-A (abd-A) genes within a negatively regulated target, the P2 promoter of the Antennapedia (Antp) gene. By systematically mutagenizing binding sites and observing the resulting P2 expression pattern in embryos, we have found evidence for cell-type-specific interactions that are mediated by these sequences. In certain neuronal cells, UBX and ABD-A proteins appear to repress by competing for common binding sites with another homeodomain protein, which we propose to be ANTP acting to induce P2 transcription in an autoregulatory manner. In sets of cells that contribute to the tracheal system, UBX and ABD-A repress by counteracting the function of a factor acting at independent sites. The latter mechanism of repression requires only that multiple homeodomain binding sequences be present and is not dependent on any particular binding site.